2020
DOI: 10.1038/s41598-020-75834-8
|View full text |Cite
|
Sign up to set email alerts
|

Preconditioning the immature lung with enhanced Nrf2 activity protects against oxidant-induced hypoalveolarization in mice

Abstract: Bronchopulmonary dysplasia (BPD) is a chronic disease of preterm babies with poor clinical outcomes. Nrf2 transcription factor is crucial for cytoprotective response, whereas Keap1—an endogenous inhibitor of Nrf2 signaling—dampens these protective responses. Nrf2-sufficient (wild type) newborn mice exposed to hyperoxia develop hypoalveolarization, which phenocopies human BPD, and Nrf2 deficiency worsens it. In this study, we used PND1 pups bearing bearing hypomorphic Keap1 floxed alleles (Keap1f/f) with increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Several approaches have tested the potential of augmenting Nrf2 activity, including preconditioning of the lung by targeting Keap1 and treatment with rapamycin, which resulted in increased baseline Nrf2 levels and antioxidant capacity. While the inflammatory response to hyperoxia was not altered in Nrf2-augmented mice, hypoalveolarization was markedly reduced [4,55]. In recent years, it has become clear that miRNA regulations constitute key events in the pathogenesis of BPD in hyperoxic injury models, and comparable changes have been documented in infants with BPD [56].…”
Section: Gene Regulation and Epigenetic Alterationsmentioning
confidence: 89%
“…Several approaches have tested the potential of augmenting Nrf2 activity, including preconditioning of the lung by targeting Keap1 and treatment with rapamycin, which resulted in increased baseline Nrf2 levels and antioxidant capacity. While the inflammatory response to hyperoxia was not altered in Nrf2-augmented mice, hypoalveolarization was markedly reduced [4,55]. In recent years, it has become clear that miRNA regulations constitute key events in the pathogenesis of BPD in hyperoxic injury models, and comparable changes have been documented in infants with BPD [56].…”
Section: Gene Regulation and Epigenetic Alterationsmentioning
confidence: 89%
“…Nrf2 is dissociated from Keap1 and transferred to the nucleus under the stimulation of oxidative stress, phosphorylation or electrophiles. 50 HO-1 and NQO1 are the key downstream factors of Nrf2 signal transduction, which are very important in protecting cells from the oxidative damage. 51,52 Recent studies have shown that trimetazidine can delay the formation of age-related cataracts by regulating the expression of Nrf2 and reducing the production of ROS.…”
Section: Discussionmentioning
confidence: 99%
“…AREs are found in many antioxidant genes and are responsible for upregulating cellular defenses (NRF2 pathway reviewed in [23]). Enhancement of the NRF2 activity has demonstrated protective effects in several models of lung injury [24][25][26][27][28]. As a result, modulation of NRF2 has become an attractive drug target for inflammatory diseases (reviewed in [27]).…”
Section: Discussionmentioning
confidence: 99%